Condições ecológicas e predição de áreas adequáveis para ocorrência de Lonomia obliqua Walker 1855 no Brasil - Favalesso, Marília Melo (2018)
Lonomia obliqua Walker 1855 (Saturniidae: Hemileucinae) is a species of moth of sanitary interest in Brazil. Their larvae are etiological agents of lonomism, a form of erucism caused by the contact of the human beings with the stinging structures of the species. The most worrying symptoms of lonomism are the systemic hemorrhagic conditions that can lead to several outcomes, including death. The first official notifications of accidents with the species date back to the end of the 80s, in the state of Rio Grande do Sul. Since then, several accidents have been documented in Brazil, mainly in the south and southeast regions of the country. With the increase in the number of victims, health authorities in the state of São Paulo, represented by the “Instituto Butantã”, developed an anti-lonomic serum, which is distributed by the Ministry of Health in places with a higher prevalence of accidents. Hypotheses have been raised on the relation between the growth of the cases of lonomismo and the human occupation; however, little is known about the spatial distribution and ecological aspects of the species to enable the testing of these hypotheses. In view of the above, the present study aimed to produce a map for the potential geographical distribution of L. obliqua in Brazil, based on the combination of different ENM (Ecological Niche Modeling) algorithms. A total of 38 occurrence points were distributed across the geographic area of Brazil and Misiones, Argentina, which were partitioned for calibration and evaluation of the distribution model. Eight continuous climatic variables and only 16 previously considered variables were selected. Different ENM methodologies were tested and compared to TSS (True Skill Statistic) index values. The final model-map was composed of a combination of four algorithms (Gower, Mahalanobis, Maxent and SVM), with pseudo-absences outside a bioclimatic envelope and a number of pseudo-absences equal to that of presences. This model map was binarized from the Low Presence Threshold (LPT) and cut only for Brazil. According to this model map, the areas predicted as suitable for L. obliqua would be restricted to latitudes ~12° and ~32°, and longitudes ~39° and ~57°. When evaluating new sites of occurrence of the specie in Rio Grande do Sul, it was possible to verify that all the municipalities were in areas predicted by the model-map. A characterization of the abiotic variables related to the niche of the specie was also carried out, being these extracted from the area predicted as adequate the presence of the specie in the model map. To help characterize these variables, we also extract categorical descriptors of climate, soil and vegetation (in %). The percentage of land use classes was also extracted in order to contribute to the hypothesis that condition the increase of accidents due to human occupation. In this question, we find a large part of the area predicted within classes of agricultural soils in Brazil, which leads us to ratify the current hypotheses. Thus, the loss of habitat of the species for the agricultural enterprises increases the human contact with the specie, which should increase the number of notifications of the lonomism, generating greater epidemiological concern and habitat conservation for this specie.